Report of the Wintering Party of the 11th Japanese Antarctic Research Expedition in 1970-1971 (Reports of the Japanese Antarctic Research Expedition) - Tatsuro MATSUDA (National Institute of Polar Research, 1972)
1. The 11th Wintering party of the Japanese Antarctic Research Expedition (1969-1971) led by T. MATSUDA consisted of thirty members. The items of the research programmes were as follows : aurora, cosmic rays, geomagnetism, ionosphere, radio physics, infrasonic pressure waves, meteorology, biology, oceanography, seismology, cartography, glaciology, medical science, and sounding rocket research. 2. Mizuho Camp (70°42.1'S, 44°17.5'E) was established on 21 July 1970 by the inland traverse party led by H. SHIMIZU. In summer season the inland traverse party made a 81-day trip from 3 November 1970 to 22 January 1971. The main object was traverse glaciology and studies of meteorology, cartography, gravity, geomagnetism and medical science were carried out. 3. At Syowa Station, 45kVA and 65kVA diesel electric generators were maintained without power failures. The water supply is most important for the life in the Antarctic. A 130kl water tank was installed at the Station, and the water in this tank was warmed by heat-exchangers of generators. The water was supplied from the reservoir to 130kl water tank throughout the year. The water (about 300 tons) in the reservoir was kept from freezing by the use of a 5kW electric heater set at the bottom. The water supply system at Syowa Station was completed and the cold water and hot water were supplied constantly. Stations that communicated with Syowa Station were Chosi (Japan), KDD (Japan), Mawson, Molodezhnaya and the ice breaker FUJI.